2002
DOI: 10.1530/rep.0.1240409
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 8 in the cervix of non-pregnant ewes

Abstract: Studies of cervical artificial insemination of ewes at hormone-synchronized oestrus indicate that the cervix remains relatively impenetrable to semen, in contrast to naturally breeding animals. During parturition the inflammatory response plays an important part in cervical dilation and possibly, to a lesser extent, in the non-pregnant cervix at oestrus to facilitate the transcervical transport of semen. The expression of interleukin 8 (IL-8), a pro-inflammatory cytokine in the ovine cervix, has been mapped an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Since CXCL8 is fundamental for the migration and activation of neutrophils, it is expected to be elevated in diseased animals [ 3 , 6 , 31 ]. Serum CXCL8 levels in dogs with pyometra have seldom been analyzed, but it has been shown that various cell types within the uterus produce CXCL8 in response to diverse stimuli, including pyometra [ 5 , 11 , 16 , 30 ]. The source of CXCL8 measured in sera is unknown and so, a local as well as a systemic secretion has to be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since CXCL8 is fundamental for the migration and activation of neutrophils, it is expected to be elevated in diseased animals [ 3 , 6 , 31 ]. Serum CXCL8 levels in dogs with pyometra have seldom been analyzed, but it has been shown that various cell types within the uterus produce CXCL8 in response to diverse stimuli, including pyometra [ 5 , 11 , 16 , 30 ]. The source of CXCL8 measured in sera is unknown and so, a local as well as a systemic secretion has to be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Second, low serum CXCL8 values can be due to a poor or depleted immune response and thus be related to severe symptoms. Third, progesterone is an inhibitor of CXCL8 in uteri and makes this organ more susceptible to infection [ 5 , 16 , 28 , 29 , 31 ]. If the CXCL8 in sera stems from the uterus, its decrease may be the result of high progesterone concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, there were no apparent differences in the abundance or localization of GLUT‐1 and GLUT‐3 mRNA in placentomes following cortisol infusion. In situ hybridization is widely accepted as a sufficiently robust and accurate method for quantifying gene expression and has the added advantage of establishing the cellular localization of the specific mRNAs (Gadd et al 2000; Mitchell et al 2002). Although further studies are required to determine whether cortisol affects expression of GLUT proteins in ovine placentomes, the current observations suggest that changes in transporter abundance are unlikely to make a major contribution to the cortisol‐induced decrease in umbilical glucose uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Automated sequencing was performed to verify the sequences. Messenger RNA levels were quantified by in situ hybridisation, on 20 μm thick coronal hypothalamic cryo‐sections, using techniques described in detail elsewhere (Mitchell et al 2002). Briefly, slides were fixed in 4% (w/v) paraformaldehyde in 0.1 mol l −1 phosphate‐buffered saline (PBS) for 20 min at room temperature, washed in PBS, incubated in 0.1 mmol l −1 triethanolamine for 2 min and acetylated in 0.1 mmol l −1 triethanolamine and 0.25% (v/v) acetic anhydride for 10 min.…”
Section: Methodsmentioning
confidence: 99%